Study on civil liability of referees in the sport competitions - Mohamadinejad, A.; Mirsafian, H.; Soltanhoseini, M. (Journal of Human Sport & Exercise, 2012)
Litigation is now a common occurrence and the sport environment is not excluded. The law affects all aspects of sport, whether you are an Olympic champion, a referee of a soccer game, a fan of special team, a constructor or seller of sports equipment, or a coach of team. Many circumstances do occur in the field of sports through which administrators, coaches, referees, et cetera, could be entangled in legal disputes on the conducts of their duties in sports. With of referee`s career in the sport competitions and the effective role of them in the result of matches regards to the importance, discussion about the duties of referees, their responsibilities arising from breaching their duties, required factors for imposing liability to them, and the criteria of the standard referees are important. In this article, it is tried to analyze different aspects of civil liability of referees in the sport competitions.